APPLICATION OF THE 4K MODEL IN INTERNATIONAL ASSESSMENT PROGRAMS (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
V dannoy state rassmatrivaetsya nedrenie model 4K v international programmy otsenki v obrazovatelny process v sootvetstvii s bovaniyami gosudarstvennyx obrazovatelnyx standardsov i formorovanie yuchevyx competence u obchayushchixsya.